Baseline nickel level in saliva and urine among healthy Malay population / Nadia Izyan Muhamad Sabri, Indah Yuri Noviaranny and Jamil Ahsan Kazi - Muhamad Sabri, Nadia Izyan; Noviaranny, Indah Yuri; Jamil Ahsan, Kazi (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Objectives: Nickel is one of the common trace metal element used in industries. It has been documented that even in small quantities, prolonged exposure to nickel is cytotoxic, genotoxic and carcinogenic. Nickel biomonitoring has been done by various countries to monitor nickel level. However, there is little information on established baseline nickel level in our population which leads to the difficulty for comparison during nickel exposure. This study aims to determine the baseline nickel level in saliva and urine samples for the healthy Malay population. Materials and Methods: Fourteen healthy Malay subjects were recruited in this study. Saliva and urine samples were collected and analysed using Inductively Coupled Plasma Optical Mass Spectrometry (ICP-MS) to measure the nickel level. Statistical analysis was performed using IBM SPSS Version 27. Results: Results showed that the nickel level in urine was higher compared to saliva. The baseline nickel level exhibited in saliva was 4.80 ppb (95% CI: 2.23, 7.38) and in urine was 5.88 ppb (95% CI: 3.49, 8.27). Conclusion: To our knowledge, this is the first study to report the baseline nickel level in saliva and urine among the Malay population.